Flexural strengthening of RC beams via external prestressing - Ng, CK (Universiti Malaysia Sarawak, UNIMAS, 2005)
This paper describes the ability of external prestressing in enhancing the flexural strength of reinforced concrete beams quantified by the flexural strengthening ratio.